2014
DOI: 10.1177/1357633x14533885
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of the contribution of telemicroscopy to the diagnosis and management of skin tumours in teledermatology

Abstract: Dermatology images can be acquired using a miniature handheld digital microscope at magnifications of 10- to 30-fold. We investigated the contribution of telemicroscopy to the reliability and accuracy of teledermatology for skin tumours. In a retrospective study of the reliability of diagnosis and management plans, two dermatologists compared teledermatology with face-to-face assessment. We also measured the accuracy of diagnosis by comparing teledermatology with histopathological examination. Two dermatologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
1
13
0
1
Order By: Relevance
“…These studies reported agreement between telediagnosis and the reference standard of 51% to 100%. 10,26,27,36 When separating malignant and benign lesions, telediagnoses of malignant lesions were histopathologically confirmed in 62% to 100% of cases, depending on the study. Of note, the study reporting 100% agreement between telediagnosis and histopathological diagnosis for malignant lesions only included 8 malignant lesions.…”
Section: Diagnostic Accuracymentioning
confidence: 99%
See 3 more Smart Citations
“…These studies reported agreement between telediagnosis and the reference standard of 51% to 100%. 10,26,27,36 When separating malignant and benign lesions, telediagnoses of malignant lesions were histopathologically confirmed in 62% to 100% of cases, depending on the study. Of note, the study reporting 100% agreement between telediagnosis and histopathological diagnosis for malignant lesions only included 8 malignant lesions.…”
Section: Diagnostic Accuracymentioning
confidence: 99%
“…Eight studies (7 including dermoscopy) reported the diagnostic accuracy of teledermatology consultations 10,11,17,18,26,27,35,36 ( Table 4). Three of the 8 studies also assessed accuracy of FTF diagnosis compared with histopathological diagnosis, and compared the level of accuracy for FTF diagnoses with teledermatology diagnoses.…”
Section: Diagnostic Accuracymentioning
confidence: 99%
See 2 more Smart Citations
“…Digital microscopy was previously used in dermatology practice for the evaluation of morphology of molluscum contagiosum and seborrhoeic keratosis. 17,18 S ßenel et al 19 recently reported that digital microscopy increased significantly the diagnostic and therapeutic reliability of teledermatologic application in skin tumours. As far as we are aware, the present study is preliminary to perform an evaluation of the digital microscopic features of dermatofibroma.…”
Section: Features Of Dermatofibromamentioning
confidence: 99%